Therapeutic strategies for gastric cancer targeting immune cells: Future directions - Zhao, Yan; Bai, Yuansong; Shen, Meili; Li, Yapeng (Frontiers in Immunology, 2022)
Gastric cancer (GC) is a malignancy with a high incidence and mortality, and the emergence of immunotherapy has brought survival benefits to GC patients. Compared with traditional therapy, immunotherapy has the advantages of durable response, long-term survival benefits, and lower toxicity. Therefore, targeted immune cells are the most promising therapeutic strategy in the field of oncology. In this review, we introduce the role and significance of each immune cell in the tumor microenvironment of GC and summarize the current landscape of immunotherapy in GC, which includes immune checkpoint inhibitors, adoptive cell therapy (ACT), dendritic cell (DC) vaccines, reduction of M2 tumor-associated macrophages (M2 TAMs), N2 tumor-associated neutrophils (N2 TANs), myeloid-derived suppressor cells (MDSCs), effector regulatory T cells (eTregs), and regulatory B cells (Bregs) in the tumor microenvironment and reprogram TAMs and TANs into tumor killer cells. The most widely used immunotherapy strategies are the immune checkpoint inhibitor programmed cell death 1/programmed death-ligand 1 (PD-1/PD-L1) antibody, cytotoxic T lymphocyte–associated protein 4 (CTLA-4) antibody, and chimeric antigen receptor T (CAR-T) in ACT, and these therapeutic strategies have significant anti-tumor efficacy in solid tumors and hematological tumors. Targeting other immune cells provides a new direction for the immunotherapy of GC despite the relatively weak clinical data, which have been confirmed to restore or enhance anti-tumor immune function in preclinical studies and some treatment strategies have entered the clinical trial stage, and it is expected that more and more effective immune cell–based therapeutic methods will be developed and applied.